Efecto de un programa de ejercicios fisioterapéuticos sobre el desempeño físico en adultos mayores institucionalizados - Chávez Pantoja, Mariana (2014)
Objective: To evaluate changes in physical performance in institutionalized older adults through a program of physiotherapy exercises. Materials and methods: We conducted a quasi-experimental study in adults over 60 years institutionalized in Lima, Peru. The exercise program was implemented in 45 minutes sessions included warming, muscle strengthening exercises, balance, gait training and cooling phase, three times a week for 12 weeks. Physical performance was measured with the Short Physical Performance Battery (SPPB) one week before and after the intervention. It included 45 participants, which 16 didn’t attend any of the sessions and was like control group. Results: The average age was 77.6±7.1 years, 62.2% were women. The mean baseline SPPB was 7.0±1.6 in the intervention group and 6.9±1.9 in the control group (p = 0.90). It shows a change in SPPB of 2.6±1.8 in the intervention group versus -1.4±2.0 in the control group (p<0.001). Conclusions: The development of a physiotherapy exercise program for institutionalized elderly increases physical performance, which could be implemented in care centers for elderly.